Dialogues about mathematics and the structuring dimensions of educational practice: conflicts between realities (Research, Society and Development, 2022)
This article presents an excerpt from the master's dissertation in education at the Federal University of Piauí – UFPI, on the structuring dimensions of educational practice and the challenges of teaching Mathematics, which analyzes the participants' conceptions about the object of study, which are managers, pedagogical coordinators and teachers of the municipal education network of Alto Longá, Piauí, Brazil. The methodological theoretical framework is configured as qualitative research of the descriptive type with a narrative approach. Faced with the educational demands and concerns as a teacher and teacher trainer, we sought to understand how the mathematics teacher articulated the structuring dimensions of educational practice in the early years of elementary school to enable students' learning?. In this writing we have the answers referring to the initial objective, which would be to identify the teachers' conceptions about the structuring dimensions of educational practice, a semi-structured questionnaire with closed and open questions was used to collect data that were organized into categories, according to Bardin, with contributions from the IRAMUTEQ lexical analysis software, and interpreted using the discourse analysis technique. The results emphasized by the participants reveal a range of possibilities that appeared in the course of the speeches as essential elements: training, context, pedagogical guidelines, trends, methodologies, methods, planning, intervention and evaluation, in addition to the socio-emotional perspective of both involved in the process educational.